(untitled) (Philological Studies, 2025)
This paper analyses Velika skitija (1969), the collection of poems by Miodrag Pavlović, using the theory of cultural memory of Jan Assmann (2007), an egyptologist, cultural theorist and religious scholar. Velika skitija covers a number of topics important for the establishment of a culture of memory: the relationship between the individual and the collective, speech and writing, history and myth, history and memory, the transition of memory into history and vice versa, as well as the poetic link between poetry and ritual. Of particular importance for the analysis is the relationship of Velika skitija with the Middle Ages, as analyzed by Marko Radulović (2017; 2020). Starting from these features, which have been observed in the literature related to Pavlović’s work –especially the chosen collection of poems – the collection is illuminated in the context of the culture of memory. The ultimate goal of this analysis is to contribute to the understanding of the ways of addressing the metaphysical void and the role of memory in the constitution of the poet’s voice and the entire collection of poems. Particular attention is paid to the relationship between the individual and history, which is considered using the categories of communicative and cultural memory. The analysis showed that within the collection some features of the culture of memory are thematized, while it is fully realized in the process of reception. This paradigm helped us to encompass the simultaneous constructivist passage through history and the search for the transcendence of Velika skitija in a comprehensive and mildly deconstructivist manner.